THYROIDAL STATUS IN CHILDREN WITH VARIOUS DEGREE OF INCREASE OF THYROID GLAND WHO LIVE IN ECOLOGICALLY UNFAVORABLE AREA OF TRANSBAIKALIA - E. V. Selina; G. I. Bisharova; T. A. Chuprova (Acta Biomedica Scientifica, 2012)
We performed the research of thyroidal status in children with endemic goiter who live in ecologically unfavorable area of Transbaikalia. Frequency distribution of endemic goiter was analyzed, depending on a sex and age